Meningkatkan Kesadaran Respek Siswa Sekolah Dasar dengan Biblioedukasi - Safitri, Innaha Fahrish; Handarini, Dany Moenindyah; Mappiare-AT, Andi (citeus, 2021)
Respect contributes to restraining the frequently occur acts of violence. Biblio education belongs to one of the means to establish respect. This study aims to investigate the efficacy of Biblio Education in improving elementary students' awareness of respect. This quantitative study employs an equivalent time-series design with ten subjects from State Elementary School of Gadingkasri, selected through purposive sampling. It used Biblio Education treatment in eight meetings. A validated and reliable respect awareness scale was used as the measuring instrument. The data were analyzed using non-parametric data analysis of the Wilcoxon Signed Rank Test. The results reveal that the 1-4 treatments carry no effect on students' awareness of respect. Its impact on students' awareness of respect is observed in treatments 5-8. Comprehensively, Biblio Education is sufficient to enhance elementary school students' awareness of respect.